2011
DOI: 10.1016/j.lwt.2010.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Optimum controlled atmospheres minimise respiration rate and quality losses while increase phenolic compounds of baby carrots

Abstract: a b s t r a c tBaby carrot is a very perishable product mainly due to the abrasion of the cylindrical carrot root segments. The influence of four different controlled atmospheres (CA) (air, 2 kPa O 2 þ 15 kPa CO 2 , 5 kPa O 2 þ 5 kPa CO 2 and 10 kPa O 2 þ 10 kPa CO 2 ) was studied to maintain quality and prolong the shelf life of baby carrots. Respiration rate (RR), the content of vitamin C, carotenoids and phenolics by HPLC as well as the sensory quality of baby carrots during storage at 4 C were evaluated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Phenolic acids accumulated in all processed and the untreated carrots during cold storing at 8 °C. This was in accordance with several studies dealing with the induction of phenolic acids in wounded carrot products [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. However, according to Alarcόn-Flores et al [ 7 ] commercial fresh-cut carrots contained lower levels of phenolic acids than the fresh counterpart.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Phenolic acids accumulated in all processed and the untreated carrots during cold storing at 8 °C. This was in accordance with several studies dealing with the induction of phenolic acids in wounded carrot products [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. However, according to Alarcόn-Flores et al [ 7 ] commercial fresh-cut carrots contained lower levels of phenolic acids than the fresh counterpart.…”
Section: Resultssupporting
confidence: 92%
“…Several research groups have stated that the content of phenolics and the antioxidative capacity of carrots subjected to minimal processing could increase during storage [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Most of these studies have followed the concentration of only a few or one phenolic acid or even the total phenolic content [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang and Hamauzu [8] found that carrots contained mainly hydroxycinnamic acid derivatives, among them chlorogenic acid represented 42.2–61.8 % of total phenolics. Chlorogenic acid is also accumulated in baby carrot roots [9], this compound accompanied by ferulic and dicaffeoylquinic acid reached 82 % of total phenolics in wounded root tissue [10]. Chlorogenic acid, caffeic acid, p -hydroxybenzoic acid, ferulic acid and other cinnamic acid isomers predominated in carrots of different colors [3].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of controlled and modified atmosphere storage on the shelf life of whole and cut products is well known. The optimal atmosphere for storage of whole and fresh‐cut products is well documented because there are many studies available on sliced zucchini, shredded iceberg lettuce and onions, carrots, kiwifruits, pineapples, and many others. On the other hand, few studies are available on the effect of atmospheric conditions before processing on the quality of minimally processed products.…”
Section: Impact Of Postharvest Handling Of Raw Materials On Cut Producmentioning
confidence: 99%